Pengaruh Penggunaan Model Discovery Learning terhadap Hasil Belajar dan Aktivitas Siswa pada Pembelajaran IPAS di Kelas V SDN 060928 - Tiana Nurjannah Rifai; Hidayat Hidayat (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study aims to explore the influence of the Discovery Learning model on student learning outcomes and to assess the level of student learning activity on the material of light properties. The type of research used is Quasi Experiment. The study population included all fifth grade students of SDN 060928, with samples taken from 30 students of class VA who applied the Discovery Learning model, while class VB used the conventional learning model. The study began with a pretest, followed by a posttest after the implementation of the Discovery Learning model. The instruments used consisted of a test in the form of 20 multiple-choice questions to measure learning outcomes and an observation sheet to assess student activity. Data analysis tools include validity, reliability, discrimination, and difficulty level tests. Statistical analysis techniques include normality tests, homogeneity tests, two-mean difference tests, and hypothesis tests. Based on the results of the hypothesis test, the average learning outcome in the experimental class was 77.66, higher than the control class which only reached 62.16. In addition, student learning activities in the experimental class using the Discovery Learning model showed a significant level of activity with an average value of 76.30. The use of the Discovery Learning model has a positive effect on student learning outcomes and activities in science learning on the properties of light.